The impact of digital marketing on consumer behavior - Khudoyberdieva Olima Otabek kyzy (THE INNOVATION ECONOMY, 2026)
This research paper examines the impact of digital marketing on consumer behavior, particularly consumer behavior. It examines the impact on information search, evaluation, purchase, and brand engagement. The paper assesses the impact of digital marketing quantitatively and qualitatively, including through website analytics, social media data, and survey results. The research findings demonstrate that digital marketing has a significant impact on consumer decision-making.The research findings demonstrate that online opinions, social media, and mobile marketing play a significant role in the decision-making process.The paper also discusses the ethical principles of digital marketing, the use of personal data, and advertising.